KEMAMPUAN MENERJEMAHKAN KALIMAT BAHASA MAKASSAR KE DALAM BAHASA INDONESIA MELALUI MEDIA POWER POINT SISWA KELAS IV SD INPRES JIPANG KABUPATEN GOWA: ABILITY TO TRANSLATE MACASSAR LANGUAGE SENTENCES INTO INDONESIAN THROUGH POWER POINT MEDIA FOR GRADE IV STUDENTS OF INPRES JIPANG ELEMENTARY SCHOOL, GOWA DISTRICT - Indah, Nur; Daeng, Kembong; Asri, Aswati (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2025)
This study aims to describe the ability to translate Makassar language sentences into Indonesian through powerpoint media for students. This type of research is quantitative research in the form of quantitative descriptive. The population in this study were all fourth grade students of SD Inpres Jipang, totalling 32 people. The sample set was 32 students using saturated sampling technique. The data collection technique used is a test technique, namely a written test. The data collected will be analysed using descriptive statistical techniques. The results showed that the ability to translate Makassarese sentences into Indonesian through powerpoint media of students was in the category of not yet able with an average score obtained by students as a whole of 48.7. The level of ability to translate Makassarese sentences into Indonesian through powerpoint media of students, namely samples who obtained scores of 75-100, did not meet the criteria for the level of student ability to reach the predetermined standard of 75%. The students who scored 75-100 were 6 students (18.8%) who were in the able category and students who scored 0-74 were 26 students (81.2%) who were in the unable category.